Altered Relationships Between rCBF in Different Brain Regions of Never-Treated Schizophrenics - Sabri, O.; Erkwoh, R.; Schreckenberger, M.; Cremerius, U.; Owega, A.; Diekmann, C.; Schulz, G.; Zimny, M.; Sass, H.; Buell, U. (Nuklearmedizin - NuclearMedicine, 1997)
Aim of this study was to investigate the relations between regiona cerebral blood flow (rCBF) of different brain regions in acute schizophrenia and following neuroleptic treatment.Methods: Twenty-two never-treated, acute schizophrenic patients were examined with HMPAO brain SPECT and assessed psychopathological-ly, and reexamined following neuroleptic treatment (over 96.8 days) and psychopathological remission. rCBF was determined by region/cerebel-lar count quotients obtained from 98 irregular regions of interest (ROIs), summed up to 11 ROIs on each hemisphere. In acute schizophrenics, interregional rCBF correlations of each ROI to every other ROI were compared to the interregional correlations following neuroleptic treatment and to those of controls.Results: All significant correlations of rCBF ratios of different brain regions were exclusively positive in controls and patients. In controls, all ROIs of one hemisphere except the mesial temporal ROI correlated significantly to its contralateral ROI. Each hemisphere showed significant frontal-temporal correlations, as well as cortical-subcortical and some cortico-limbic. In contrast, in acute schizophrenics nearly every ROI correlated significantly with every other ROI, without a grouping or relation of the rCBF of certain ROIs as in controls. After neuroleptic treatment and clinical improvement, this diffuse pattern of correlations remained.Conclusions: These results indicate differences in the neuronal interplay between regions in schizophrenic and healthy subjects. In never-treated schizophrenics, diffuse interregional rCBF correlations can be seen as a sign of change and dysfunction of the systems regulating specificity and diversity of the neuronal functions. Neuroleptic therapy and psychopathologic remission showed no normalizing effect on interregional correlations.
Keywords: HMPAO brain SPECT; rCBF; never-treated schizophrenics; PANSS; neuroleptic treatment; interregional correlations